Global change and the earth system : a planet under pressure - Steffen, William J.; Sanderson, A.; Tyson, P. D.; Jäger, J.; Matson, P. A.; Moore, B. III; Oldfield, F.; Richardson, K.; Schellnhuber, H. J.; Turner, B. L. II; Wasson, R. J. (Array, 2005)
Sadržaj: 1. An integrated Earth system ; 2. Planetary machinery: the dynamics of the Earth prior to significant human influence ; 3. The anthropocene era: how humans are changing the Earth system ; 4. Reverberations of change: the responses of the Earth system to human activities ; 5. Living with global change: consequences of changes in the Earth system for human well-being ; 6. Towards Earth system science and global sustainability